PENGARUH KONSENTRASI BAP DAN NAUNGAN TERHADAP KEBERHASILAN DAN PERTUMBUHAN SAMBUNG SISTEM KAKI GANDA BIBIT DURIAN (Durio zhibertinus L.) - Ruben Natanael Pratama Siahaan; Andi Apriany Fatmawaty; Abdul Hasyim Sodiq; Andree Syailendra (Gunung Djati Conference Series, 2023)
Durian (Durio zhibertinus L.) is one of the most popular fruits in the tropics. The grafting technique is a common technique for propagation or propagation of durian in commercially cultivated durian plantations. Cytokinins are growth regulators used in plant nurseries because they play an important role in cell division in tissues and encourage tissue differentiation in the formation of shoots. High light intensity affects auxin activity in the apical meristem. When the light intensity is high, the auxin activity increases. This research is an experimental study. The research will be carried out in December 2022 - February 2023 at the Karang Kitri Experimental Garden, Faculty of Agriculture, Sultan Ageng Tirtayasa University. The design responses in this study included Percentage of Life Connections (%), Age at Bud Break (Day After Grafting/DAG), Number of Opened Leaves (strands), Increase in Length of Entres (cm), Diameter of Entres (cm). Based on the results and discussion, it can be concluded as follows that: (1.) Treatment of BAP (Benzyl Amino Purine) 100 ppm gave the best effect on parameters of shoot rupture age (DAG), leaf greenness index, increase in shoot length (cm), and on increase in rootstock diameter (mm). (2.) Shading treatment of 80% gave the best effect on the parameters of shoot rupture age (DAG), and the number of open leaves (strands). (3.) There is an interaction between the effect of shade and the effect of giving BAP (Benzyl Amino Purine) concentrations on the parameter of bud break age (Day After Grafting/DAG) in N3B1 plants (17 DAG).